1999
DOI: 10.22358/jafs/68805/1999
|View full text |Cite
|
Sign up to set email alerts
|

Flux of amino acids and peptides across the portal vein-drained tissue of pigs

Abstract: An experiment was carried out to determine the flux of amino acids across the portal veindrained tissue into and out of the plasma and red blood cell free amino acid pools and the plasma peptide pool of the portal vein blood of growing pigs. Four pigs, fitted with catheters in a carotid artery and the portal and mesenteric veins, were fed a maize starch-based diet with wheat gluten as protein source. The feed was given daily at the level of 2% body weight as a wet mash (1:2, w/v water) in two equal meals at 08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The presence of the CP4 EPSPS protein, either whole or in fragments, was not measured but only contributed an estimated 83 µg to 406 g of daily CP intake. A substantial proportion of dietary protein can be absorbed as peptides in pigs (Caine et al 1999) and these can have metabolic effects. However, the lack of any differences between the PCC and RRC dietary treatments indicated that even if any fragments of exogenous protein were present in visceral tissues, they did not impact the productive performance or pork quality of pigs in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the CP4 EPSPS protein, either whole or in fragments, was not measured but only contributed an estimated 83 µg to 406 g of daily CP intake. A substantial proportion of dietary protein can be absorbed as peptides in pigs (Caine et al 1999) and these can have metabolic effects. However, the lack of any differences between the PCC and RRC dietary treatments indicated that even if any fragments of exogenous protein were present in visceral tissues, they did not impact the productive performance or pork quality of pigs in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that peptide AA may represent from 0.67 to 0.77 of total NPA of AA in Iberian pigs (Fernández-Fígares et al, 2019). Caine et al (1999) reported that free AA represented the greatest proportion of NPA of AA. In any case, the contribution of peptide AA to NPA of AA is remarkable (Gilbert et al, 2008).…”
Section: Tablementioning
confidence: 99%